2022
DOI: 10.33425/2690-537x.1023
|View full text |Cite
|
Sign up to set email alerts
|

Moderna Arm Cutaneous Side Effect of Moderna Vaccine among Healthcare Providers in Secondary Hospital in Jakarta - Tangerang, Indonesia.

Abstract: Introduction: Since the emerging Delta variant of COVID-19 in 2021, the World Health Organization (WHO) and Centers for Disease Control and Prevention (CDC) have encouraged world citizens to get booster vaccination. Booster vaccination has been used worldwide to prevent severe COVID-19. Healthcare providers were given the priority to be vaccinated, and the Moderna vaccine was given as chosen booster vaccination. Cutaneous side effect related to the Moderna vaccine has been reported in Public Secondary Hospital… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…The AEFI of this vaccine includes "Moderna Arm", which can appear as a localized erythematous rash within a few days after the first dose. Most of the adverse effects are resolved spontaneously, but topical steroids and oral histamine have shown potency in relieving the rash and controlling symptoms [24]. Studies have reported that myocarditis is a rare severe systemic complication [25].…”
Section: Aefis With Systemic Symptomsmentioning
confidence: 99%
“…The AEFI of this vaccine includes "Moderna Arm", which can appear as a localized erythematous rash within a few days after the first dose. Most of the adverse effects are resolved spontaneously, but topical steroids and oral histamine have shown potency in relieving the rash and controlling symptoms [24]. Studies have reported that myocarditis is a rare severe systemic complication [25].…”
Section: Aefis With Systemic Symptomsmentioning
confidence: 99%